Before the dawn : an autobiography - Adams, Gerry, 1948- (2018)
"In this fascinating memoir of his early life, Gerry Adams, the president of Sinn Féin, the political wing of the Irish Republican Army, describes the development of the modern "Troubles'' in Northern Ireland and his own central role in them, culminating in the tragic hunger strike by imprisoned IRA members in 1981. Born in 1948, Adams vividly recalls growing up in the working-class Ballymurphy district of West Belfast, where he became involved in the civil rights campaign in the late 1960s and was active in campaigns around issues of housing, unemployment, and civil rights. The unionist forces reacted violently to the protests, and the situation exploded into civil war. Adams recounts his growing radicalization, his leadership role in the political wing of the IRA, and the British use of secret courts to condemn republicans. Adams was a political prisoner, one of the first in the notorious Northern Irish jail Long Kesh, and underwent torture at the hands of the British authorities, which he describes in detail. Adams chronicles the dramatic hunger strikes of Bobby Sands, Francis Hughes, Raymond McCreesh, and others in 1980-81, which he initially resisted but which he now recognizes as having revitalized the nationalist movement. Before the Dawn is an engaging and revealing self-portrait that is essential reading for anyone wishing to understand modern Ireland. First published in 1996--at a time when politics in Northern Ireland was at an impasse, and the Good Friday Agreement was still many tense months away--this new edition contains a brand new introduction and epilogue written by the author, covering Adams's family, Brexit, and the peace process."--Provided by publisher.
Includes index.
Keywords: Adams, Gerry, -- 1948-; Irish Republican Army -- Biography; Sinn Fein -- Biography; Politicians -- Northern Ireland -- Biography; Legislators -- Northern Ireland -- Biography; Politicians -- Ireland -- Biography; Northern Ireland -- Politics and government -- 1968-1998.; Ireland -- Politics and government -- 1949-